LB2. Switch to Doravirine/Lamivudine/Tenofovir Disoproxil Fumarate (DOR/3TC/TDF) Maintains Virologic Suppression Through 48 Weeks: Results of the DRIVE-SHIFT Trial. (26th November 2018) - Kumar, Princy; Johnson, Margaret; Molina, Jean-Michel; Rizzardini, Giuliano; Cahn, Pedro; Bickel, Markus; Mallolas, Josep; Zhou, Yan; Morais, Cristiana; Kumar, Sushma; Sklar, Peter; Hanna, George J; et al.
Abstract: Background: Doravirine is a novel, non-nucleoside reverse-transcriptase inhibitor (NNRTI) that has demonstrated efficacy in two Phase 3 trials in treatment-naïve adults with HIV-1. Methods: This open-label, active-controlled, noninferiority (NI) trial evaluated a once-daily single-tablet regimen of doravirine 100 mg, lamivudine 300 mg, and tenofovir disoproxil fumarate 300 mg (DOR/3TC/TDF) vs. continuation of current therapy in adults with HIV-1 virologically suppressed for ≥6 months on a stable regimen of two NRTIs plus a boosted protease inhibitor (PI), boosted elvitegravir, or NNRTI. Participants with screening HIV-1 RNA <40 copies/mL, no history of virologic failure on any regimen, and no resistance to DOR/3TC/TDF were randomized (2:1) to start DOR/3TC/TDF on Day 1 (immediate switch group, ISG) or after 24 weeks (delayed switch group, DSG). The primary endpoint was the proportion (%) of participants with HIV-1 RNA <50 copies/mL (FDA snapshot approach), with the primary comparison between ISG at Week 48 and DSG at Week 24 and a secondary comparison between the groups at Week 24; the NI margin was -8%. The % of participants with HIV-1 RNA ≥50 copies/mL was also analyzed (FDA snapshot approach; NI margin 4%). Results: A total of 670 participants (447 ISG, 223 DSG) were treated and included in the analyses; 84.5% were male, 76.4% were white, and mean age was 43.3 years. At Week 24, 93.7% (419/447) of ISG vs. 94.6% (211/223) of DSG had HIV-1 RNA <50 copies/mL (difference −0.9% [−4.7, 3.0]), and 1.8% of each group had HIV-1 RNA ≥50 copies/mL. At Week 48, 90.8% (406/447) of ISG maintained HIV-1 RNA <50 copies/mL (vs. 94.6% of DSG at Week 24; difference −3.8%, 95% CI [−7.9%, 0.3%]), and 1.6% of ISG had HIV-1 RNA ≥50 copies/mL. In the ritonavir-boosted PI stratum, mean changes in fasting LDL-C and non-HDL-C at Week 24 were significantly lower ( P < 0.0001) in ISG vs. DSG (table). Rates of any AE and of drug-related AEs at Week 24 were higher in ISG vs. DSG. AEs were mild in most ISG participants (64% of those with any AE; 80% of those with drug-related AEs). Conclusion: A once-daily single-tablet regimen of DOR/3TC/TDF demonstrated non-inferior efficacy and acceptable safety compared with continuing therapy, and is an option for maintaining viral suppression in patients considering a change in therapy. Disclosures: P. Kumar, Merck, Pfizer, Janssen, : Grant Investigator and Shareholder, Research grant. GSK, Gilead, Teratechnologies, TaiMed, : Grant Investigator, Scientific Advisor and Shareholder, Consulting fee and Research grant. J. M. Molina, Merck GIlead ViiV Janssen Teva: Ad Board and Speaker's Bureau, Consulting fee. Gilead Sciences: Grant Investigator, Research support. G. Rizzardini, ViiV, Gilead Science, MSD, Angelini, and Abbvie: Board Member and Speaker's Bureau, Speaker honorarium. Gliead, ViiV, and MSD: Research Contractor, Research grant. P. Cahn, Abbvie: Grant, Research grant. Merck: Grant, Advisory Board. ViiV Healthcare: Grant, Advisory Board. M. Bickel, Merck & Co., Inc.: Research Contractor, Research grant. Y. Zhou, Merck & Co., Inc.: Employee, Salary. C. Morais, Merck Sharp & Dohme, a subsidiary of Merck & Co., Inc.: Employee and Shareholder, May hold stock/stock options in the company and Salary. S. Kumar, Merck & Co., Inc.: Employee and Shareholder, Salary. P. Sklar, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc.: Employee and Shareholder, Salary. G. J. Hanna, Merck Sharp & Dohme, a subsidiary of Merck & Co., inc.: Employee and Shareholder, May hold stock/stock options in the company. and Salary. C. Hwang, Merck Sharp & Dohme, a subsidiary of Merck & Co., Inc.: Employee and Shareholder, Salary. W. Greaves, Merck Sharp & Dohme, a subsidiary of Merck & Co., Inc.: Employee, May hold stock/stock options within the company.